Tingkat Partisipasi Anggota terhadap Koperasi Unit Desa (KUD) Mekar Sari di Desa Pulau Jambu Kecamatan Kuok Kabupaten Kampar - Eri Sayamar; Rosnita '; Rahmadsyah ' (Universitas Riau, 2007)
Participating member of Cooperation unit of Countryside represent one of indicator in finding out the efficacy of the cooperation. High participation of member could make the cooperation running smartly and dynamic. The location of this research wasb countryside of island of jambu as mean to know participation of member to KUD mekar sari, especially in knowing benefic for the member. Paying obligatory, principle and voluntary deposits., and participate member in effort activity owned by cooperation. Method used in this research was case study method. Case in this research is KUD Mekar Sari. Respondens in this were chief, manager, body of counselor and founder, manager KUD, body of supervisor and member of KUD consisted of farmer, merchant, officer and also the labour. Participating member of cooperation was calculated by using test classification. Then the values were obtained that classified into three groups; those are good, enough, and less participations. Good enough, and less criteria of value were determinate by using the value ranging from 70-100, 51-69 and ≥ 50, respectively.